Content Analysis of Blended Curriculum (virtual and non-virtual) in Nursing - Ali Toghyani; Jahanbakhsh Rahmani; Shayesteh Salehi; Marzieh Adelmehraban (Zanjan University of Medical Sciences and Health Services, 2022)
Background: Blended learning is the thoughtful integration of online and face-to-face learning, which is widely accepted in nursing education. Objectives: Despite its importance and complicacy, few studies investigated this issue. This study aimed to extend knowledge regarding factors contributing to effective blended learning in nursing education. Methods: Following the Attride-Stirling content analysis method, we searched PubMed, Elsevier, Emerald, Science Direct, ProQuest, and Springer databases and national databases of SID and MagIran to identify relevant studies using various combinations of online, semi-online, hybrid, and mixed keywords from 2005 to 2018. Results: Four main themes were identified, content, context, educational activities, and evaluation. Nine identified organizer themes were as follows: Content objectives, flexibility, control and evaluation, technological capabilities, support system, teaching activities, learning activities, performance feedback, and evaluation methods. Finally, 23 basic themes codes were obtained as factors that should be embedded in the online nursing curriculum. Conclusion: Blended learning is a rational and flexible method to improve the educational performance of nursing students. However, it should be based on need assessment, appropriate planning and execution, and evaluation and feedback.